Bioactivity of Falkenbergia rufolanosa Methanolic Extract: Assessment of Its Effect on Methyl-Thiophanate Induced Bone and Blood Disorders - Amal Feki; Intissar Kammoun; Malek Eleroui; Rim Kallel; Fatma Megdiche; Liwa Hariz; Tahia Boudawara; Choumous Kallel; Hatem Kallel; Jean Marc Pujo; Ibtissem Ben Amara (MDPI AG, 2023)
This study aimed to evaluate the potentiality of a mineral and antioxidant-rich methanolic extract of the red marine alga Falkenbergia rufolanosa (FRE) against methyl-thiophanate (MT)-induced toxicity in adult rats. The animals were allocated into four groups: controls, MT (300 mg/kg), MT + FRE, and FRE-treated group for 7 days. Our results demonstrated severe mineral perturbations due to MT treatment, especially in calcium and phosphorus levels in plasma, urine, and bone. Similarly, the hematological analysis revealed increased red blood cells, platelets, and white blood cells associated with striking genotoxicity. Interestingly, a significant rise in lipid peroxidation and advanced oxidation protein products level in erythrocytes and bone were noted. Meanwhile, a depletion of the antioxidant status in both tissues occurred. These biochemical alterations were in harmony with DNA degradation and histological variation in bone and blood. In the other trend, data showed that treatment with alga improved MT-induced hematotoxicity, genotoxicity, and oxidative stress in the blood and bone. Osteo-mineral metabolism and bone histo-architecture were also noted. In conclusion, these findings demonstrated that the red alga Falkenbergia rufolanosa is a potent source of antioxidant and antibacterial agents, as revealed by the in vitro analysis.